1989
DOI: 10.1021/ie00090a029
|View full text |Cite
|
Sign up to set email alerts
|

Supersaturation and crystallization kinetics of potassium chloride

Abstract: An experimental investigation was conducted to determine mixing quality downstream from a 90°p ipeline elbow. Mixing quality, as determined by a concentration second moment, was measured for a range of jet-to-pipe momentum ratios at both 5 and 10 pipeline diameters downstream from the jet injection point. The ratio of the centerline radius of curvature of the elbow to the pipeline diameter was varied from a mitered corner of 0.5 to a maximum value of 1.14. The injection point was located such that it entered n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 8 publications
2
29
1
Order By: Relevance
“…The first order of the growth process of KCl crystals was also found in [2,4,[8][9][10]. In work [2] the growth of KCl crystals was in the kinetic mode of process at very low supersaturation of solution.…”
Section: The Length Of the Induction Period Of The Crystallization Prmentioning
confidence: 87%
See 1 more Smart Citation
“…The first order of the growth process of KCl crystals was also found in [2,4,[8][9][10]. In work [2] the growth of KCl crystals was in the kinetic mode of process at very low supersaturation of solution.…”
Section: The Length Of the Induction Period Of The Crystallization Prmentioning
confidence: 87%
“…Crystallization of KCl in MSMPR crystallizer in the kinetic mode of the process was studied by Ru-Ying Qian at al. [9]. It was found that the growth rate was proportional to supersaturation of solution [9].…”
Section: The Length Of the Induction Period Of The Crystallization Prmentioning
confidence: 98%
“…Though the objective of this work is to show the advantages of the methodology presented we also verified the neural network for suspension crystallization by the experimental data presented by Qian et al [12,13]. They measured the crystal growth rate and nucleation rate in different sizes of crystallizers.…”
Section: Crystallizationmentioning
confidence: 62%
“…If the nucleation rate is controlled by secondary nucleation, it can be expressed by the following equation: (13) The crystal growth rate is mainly affected by the supersaturation of the solution and can be expressed as (14) where K g and g are constants to be found experimentally. Together, the population balance, mass balance, nucleation rate, and growth rate give a perfect description of crystallization.…”
Section: Crystallizationmentioning
confidence: 99%
“…The power of supersaturation dependence in growth and nucleation relations is the key parameter in this classification. Using Qian et al (1989) correlation, the growth of KCl crystals may be described by:…”
Section: Crystallization Kineticsmentioning
confidence: 99%